2001
DOI: 10.1055/s-2001-16484
|View full text |Cite
|
Sign up to set email alerts
|

Flavanone Glycosides from Citrus junos and their Anti-Influenza Virus Activity

Abstract: By bioactivity-guided fractionation, a new flavanone triglycoside, naringenin 7-O-(2",6"-di-O-alpha-rhamnopyranosyl)-beta-glucopyranoside (1), as well as hesperetin 7-O-(2", 6"-di-O-alpha-rhamnopyranosyl)-beta-glucopyranoside (2), hesperidin (3) and narirutin (4) have been isolated from the fruits of Citrus junos Tanaka (Rutaceae). In addition, hesperetin 7-O-(2",6"-di-O-alpha-rhamnopyranosyl)-beta-glucopyranoside (2) is reported for the first time from this plant and inhibits the influenza A virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 0 publications
2
37
0
1
Order By: Relevance
“…By bioactivityguided fractionation, a new flavanone triglycoside, naringenin 7-O-(2′,6′-di-O-alpha-rhamnopyranosyl)-beta-glucopyranoside (1), as well as hesperetin 7-O-(2′,6′-di-O-alpha-rhamnopyranosyl)-beta-glucopyranoside (2), hesperidin (3) and narirutin (4) were isolated from the fruits of Citrus junos v. Tanaka, Rutaceae) (Kim et al, 2001). In addition, (2) was reported for the first time from this plant and was found to inhibit the influenza A virus.…”
Section: Flavonoidsmentioning
confidence: 99%
“…By bioactivityguided fractionation, a new flavanone triglycoside, naringenin 7-O-(2′,6′-di-O-alpha-rhamnopyranosyl)-beta-glucopyranoside (1), as well as hesperetin 7-O-(2′,6′-di-O-alpha-rhamnopyranosyl)-beta-glucopyranoside (2), hesperidin (3) and narirutin (4) were isolated from the fruits of Citrus junos v. Tanaka, Rutaceae) (Kim et al, 2001). In addition, (2) was reported for the first time from this plant and was found to inhibit the influenza A virus.…”
Section: Flavonoidsmentioning
confidence: 99%
“…Recently, the existing bibliography on biological and pharmacological of these fl avonoids was reviewed (Tripoli et al, 2007). Several pharmacological studies have also shown that these fl avonoids possess anti-allergic (Inoue et al, 2002), anti-oxidant (Wang et al, 2003;Rajadurai et al, 2006), anti-infl uenza (Kim et al, 2001), anti-tumor (Vanamala et al, 2006) and anti-infl ammatory (Panthong et al, 2007) eff ects. Therefore, the screening and analysis of the fl avonoids, and extraction, separation and purifi cation of the abundant fl avonoids (narirutin, naringin and neohesperidin), is very important for the quality control and standardization of Fructus Aurantii Immaturus.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, plaque reduction assay were carried out. 8) Briefly, BHK-21 clone 15 at a final concentration of 2ϫ10 5 cell was seeded in 24-wells plates and stabilized for 24 h. Viral suspension at moi 0.02 and serial dilutions of the compounds were incubated for 1 h at 37°C, then 50 ml of each solution were added to the cells. After the 3 h of infection, cells were overlaid with 3% carboxymethylcellulose; after 24 h cells were fixed and stained with naphthol blue black, and the numbers of plaques were counted.…”
Section: Chemicalsmentioning
confidence: 99%
“…Flavanones, also called citrus flavonoids, possess many biological activities, 4) previous studies have shown its antiviral activity, hesperetin was found to inhibit the replication of herpes simplex virus type 1, poliovirus type 1, parainfluenza virus type 3 and influenza. 5,6) Hesperidin and Naringin had inhibitory activity on rotavirus infection. …”
mentioning
confidence: 99%